Políticas públicas, educação, juventude e violência na escola: quais as dinâmicas entre os diversos atores envolvidos? - Silva, Carla Regina (Universidade Federal de São Carlos, 2007)
The present relates to Violence in School according three aspects: youth of popular urban groups; violence in school and education particularly referring to a medium cycle and public school. As effect of process of social fragmentation and economic and social exclusion, it has arisen practices of violence as a social rule of wide groups present in multiple dimensions of human relations and in living together. The relationship between education and processes of violence was connected in every historical constitution of educational institutions and remains until the contemporary society, despite the conceptual transformations that supported its practices through this route. Became evident the vulnerability of youth, mainly of popular groups, given by several numbers related to violence in Country in a context, in which the public politic oriented toward to youth were recognized insufficient, fragmented, or not adequate to accomplish the requirements of that groups, according a point of view that effective them as citizens with full rights. The school has been an important achievement for poor young and teenagers in Brazil, although they have experienced a process of a widening of Medium Cycle full of difficulties and problems, such as minimum standards of quality and completeness in adequate age. Therefore, must be highlighted the importance of commitment of this study deepen and bringing to the context the phenomena of violence in school, related to the political, economical, cultural, and social conditions related to contemporarity, so that it is a urgent matter that blocks the building of democratic process in schools in daily basis. Therefore aiming getting the practices of violence in school environment evaluating the actions and situations experimented relating to this issue by different players in public schools have been worked in a empirical field that aimed five public schools in São Carlos, located in a central region of town. It s been raised related to the issue of school violence, their thoughts regarding school future perspectives of the young people e about school violence and which their way of expression and how has been their struggled. In this sense it was used applications with open and closed questions specific for each category of students and accomplished several individual interviews with employees management teachers parents and students. In the second run of search it was accomplished workshop in which has been deal with issues related to school dynamics and the expression of violence in a qualitative approach of the theme. The results were evaluated, in quantity and quality, using graphic and photographic material, as long the log and the analysis of content of the speech of the players involved. Among analysis of the data gathered, it has been refined the strategies of social inclusion and exclusion process reproduced by school, and the dynamics of school agents related to the violence processes, their reproduction and struggling. In view of density and scope of violence in present days, the school suffers internal and external factors, that are present in daily basis, and face the tough task of conciliating repressive and punishing methods with the challenge of building democratic and participative practices.
Keywords: Políticas públicas; Juventude; Ensino médio; Violência escolar; Escola democrática; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS